2006
DOI: 10.1007/s10875-006-9048-9
|View full text |Cite
|
Sign up to set email alerts
|

Programmed Death-1 Gene Polymorphisms in Patients With Systemic Lupus Erythematosus in Taiwan

Abstract: To investigate the role of programmed cell death-1 (PD-1) gene polymorphisms in the development of systemic lupus erythematosus (SLE) in Taiwan, 109 patients with SLE and 100 healthy controls were enrolled in this study. The PD-1 gene polymorphisms were determined by the method of polymerase chain reaction/restriction fragment length polymorphism. This study showed that the genotype distributions of PD-1 7209 C/T polymorphisms were significantly different between the patients with SLE and controls (P=0.002, Pc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
61
1
4

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 29 publications
2
61
1
4
Order By: Relevance
“…The genotype frequency of PD-L2 47103 T/T, in comparison with 47103 C/C, has been reported to significantly increase in patients with SLE (16). A PD-L1 gene polymorphism has not been studied yet.…”
Section: Graves' N (%)mentioning
confidence: 99%
See 1 more Smart Citation
“…The genotype frequency of PD-L2 47103 T/T, in comparison with 47103 C/C, has been reported to significantly increase in patients with SLE (16). A PD-L1 gene polymorphism has not been studied yet.…”
Section: Graves' N (%)mentioning
confidence: 99%
“…A PD-L2 gene polymorphism is associated with susceptibility to SLE (16). Newby et al (17) reported tag single nucleotide polymorphism (SNP) screening of the PD-1 gene for an association with GD.…”
Section: Introductionmentioning
confidence: 99%
“…In murine models, PD-1 deficiency causes autoimmune diseases, including systemic lupus erythematosus (SLE), depending on the genetic background (2). Of note, single nucleotide polymorphisms in the pdcd1 gene encoding PD-1 have been associated with susceptibility to SLE in humans (10,11). PD-1-deficient B6 mice developed splenomegaly, lupus-like immune complex glomerulonephritis, anti-nuclear Abs, and destructive arthritis with aging (12), whereas BALB/c mice lacking PD-1 developed a fatal autoantibody-mediated cardiomyopathy with massive thrombosis (13).…”
mentioning
confidence: 99%
“…98 However, þ 7146G/A showed a protective association with SLE in a Spanish population 100 and no association in Swedish, 101 independent Caucasian 102 and multiethnic populations including European Americans and African Americans. 103 Three genetic studies that investigated the genetic association of PDCD1 with SLE susceptibility in Chinese populations found that the þ 7146G/A SNP of PDCD1 was not associated with SLE, 104,105 whereas that of þ 7209C/T was associated with SLE susceptibility. 105 OAZ (16q12).…”
mentioning
confidence: 99%
“…103 Three genetic studies that investigated the genetic association of PDCD1 with SLE susceptibility in Chinese populations found that the þ 7146G/A SNP of PDCD1 was not associated with SLE, 104,105 whereas that of þ 7209C/T was associated with SLE susceptibility. 105 OAZ (16q12). OAZ was identified in a fine-mapping linkage study of Chinese SLE families as being associated with lupus nephritis, 106 but this result has not been replicated.…”
mentioning
confidence: 99%